The performance of ethical investment in the Nordic markets: is it profitable to invest with ethical criteria - and how ethical it actually is? - Tallgrén, Hannele (My University, 2010)
Ethical investment has experienced rapid growth around the world, reflecting the increasing awareness of investors to social, environmental, and governance issues. In recent years, issues like global warming, corporate governance and community investing have gained significant attention by governments and investors around the world. In addition, governments in western countries have taken many regulatory initiatives to stimulate ethical investment. Given the growing social awareness of investors and the increasingly positive regulatory environment, it is expectable that ethical investment will continue its growth and the relative importance as an asset class. The majority of previous studies related to ethical investment are focused on comparisons between ethical and conventional investment performance, and the main purpose of this paper is also to find out that whether ethical investments out- or underperform in relation to conventional investments in the Nordic markets. The paper also focuses on examining the relations between economic and environmental performance, and the level of environmental disclosure. A set of regression models are employed to study aforesaid relations. The sample is constructed from the OMX GES Sustainability Nordic Index and the OMX Nordic All-share Index, and company-specific variables are calculated with data drawn from the Worldscope database. The results indicate that ethical investment performance in the Nordic markets does not significantly differ from the conventional investment performance, and that good environmental performance is associated with more extensive level of discretionary environmental disclosures. The findings demonstrate that economic performance is not a significant determinant in environmental disclosure in the Nordic markets. The results give also inconsistent, yet insignificant, results about the difference in return variability between ethical and conventional investments. Investing with ethical criteria in the Nordic markets is as profitable as conventional investing, and discretionary environmental disclosures give adequate information about the ethicality of a company.
Keywords: ethical investment; company performance measurement; accounting and market measures of performance; environmental disclosure; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|